Changes in temperature of a Plinthosol cultivated with sugarcane under straw levels - Anjos, João Carlos Rocha dos; Júnior, Aderson Soares de Andrade; Bastos, Edson Alves; Silva, Everaldo Moreira da (Comunicata Scientiae, 2019)
Soil temperature is affected by its coverage and influences sugarcane productivity. Changes in temperature were assessed in a Plinthosol cultivated with sugarcane under different straw levels, as well as its reflection in stalk productivity, aiming at determining the maximum amount of straw to be removed for other purposes without damaging soil thermal conditions necessary for the crop. The experimental design was a split-plot randomized block design with four replications, with assessment periods of soil temperature arranged in the main plots, straw levels (0, 4.2, 9.5, 13.0, and 18.4 Mg ha−1) arranged in the subplots, and two measuring depths of soil temperature (0.05 and 0.10 m) arranged in the sub-subplots. Soil temperature was obtained by T-type thermocouples (copper/constantan). Soil thermal amplitude underwent oscillations as a function of straw levels, especially at a depth of 0.05 m. The maintenance of 9.5 Mg ha−1 of straw provided an increase of 11.1% in stalk productivity. Values above 9.5 Mg ha−1 of straw can be removed from the field for other purposes without impairing soil thermal conditions required for the crop.